‘We wander in your footsteps’—reciprocity and contractility in Lebanese personality-centred parties - Thuselt, Christian (British Journal of Middle Eastern Studies, 2017)
This contribution questions the widespread assumption of Lebanese parties being mere "instruments" in their leader´s hands by asking what partisans see through their chairmen. It describes an informal social contract between partisans and leaders, outlining reciprocity in interpreting the "cause", being symbolized by the latter. The core of this contract is made up by a particular interopretation of the global normativities of the modern nation state and political reciprocity. Whereas the latter might be deeply felt, it often lacks institutionalized control within the party. Finally, the contribution highlights some noticeable restrictions of this informal contractility
Keywords: Parteien; Libanon; Kataeb; Lebanese Forces; FPM